Social investments with interventions - Erola, Jani; Moisio, Pasi; Peltoniemi, Johanna (Edward Elgar Publishing, 2026)
While the Nordic model has long combined universal protection, strong public services, and inclusive social policies, recent demographic, economic, and technological pressures have exposed its limitations. We argue that extending the social investment approach with evidence-based interventions provides a more comprehensive approach to welfare research and policymaking. The chapter sets out the rationale for integrating interventions into social investment thinking, highlights the importance of effectiveness criteria and impact assessment, and presents the book's dual ambition: to strengthen the theoretical underpinnings of the social investment approach in welfare state policy and to demonstrate, through Finnish case studies, how targeted interventions can produce measurable long-term benefits.
Beyond the Nordic Welfare State : Extending Social Investments with Interventions